2021
DOI: 10.1093/cid/ciab373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emergency Medical Services Before and During the COVID-19 Pandemic in the United States, January 2018–December 2020

Abstract: Background As a result of the continuing surge of COVID-19, many patients have delayed or missed routine screening and preventive services. Medical conditions, such as coronary heart disease, mental health issues, and substance use disorder, may be identified later, leading to increases in patient morbidity and mortality. Methods The National Emergency Medical Services Information System (NEMSIS) data were used to assess 911 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 11 publications
1
40
0
1
Order By: Relevance
“…These transport and first responder services are a important part in management of time sensitive medical emergencies such as stroke and STEMI. During the pandemic increased EMS call volumes were reported compared to pre-pandemic periods placing additional strain on these services [ 52 , 53 ]. Also, delays in EMS response time including time form EMS call to scene arrival and scene arrival to door time have been reported [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These transport and first responder services are a important part in management of time sensitive medical emergencies such as stroke and STEMI. During the pandemic increased EMS call volumes were reported compared to pre-pandemic periods placing additional strain on these services [ 52 , 53 ]. Also, delays in EMS response time including time form EMS call to scene arrival and scene arrival to door time have been reported [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic increased EMS call volumes were reported compared to pre-pandemic periods placing additional strain on these services [ 52 , 53 ]. Also, delays in EMS response time including time form EMS call to scene arrival and scene arrival to door time have been reported [ 52 ]. However, the majority of studies found increased time form symptom onset to EMS call between pre-pandemic and pandemic periods [ [55] , [56] , [57] ].…”
Section: Discussionmentioning
confidence: 99%
“…The program received very positive feedback; most of the participants were satisfied to very satisfied with their experience with the program and the program’s ability to guide them through the complex OSA diagnostic pathway. This is especially meaningful considering world events during this study, which included the COVID-19 pandemic and related occupational economic, social upheavals which have been reported to interrupt medical care, as well as the widespread power outages in Texas due to weather in February 2021 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of a personal doctor, worse perceived health status, and a high burden of comorbidities were strongly related to avoiding time-sensitive emergency care among the lowest income individuals, who are already medically vulnerable and socioeconomically disadvantaged. A review of emergency medical services activations revealed a significant increase in calls related to cardiac arrest, opioid overdose, and on-scene death following the start of the pandemic [ 5 ], potentially as a consequence of deferred care. Prior studies have hypothesized that observed declines in emergency department visits during the pandemic may reflect overutilization of emergency departments for nonemergency care before the pandemic [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in medical care have occurred during the coronavirus disease 2019 (COVID-19) pandemic, especially during periods of high community transmission [ 1–3 ]. Delays in seeking care for critical or acute non-COVID-19 conditions likely contribute to excess deaths directly or indirectly attributable to COVID-19 [ 1 , 4 , 5 ]. We examined the association between sociodemographic, health-related, and COVID-19-related characteristics and avoidance of emergency medical care during the pandemic among participants in the Southern Community Cohort Study (SCCS), a prospective cohort of primarily low-income individuals in the Southeastern United States.…”
mentioning
confidence: 99%